Stronger Than My Ghosts: Narrative Exposure Therapy and Cognitive Recovery in Later Life. Issue 4 (19th May 2019) - Lely, J. C. G.; De la Rie, S. M.; Knipscheer, J. W.; Kleber, R. J.
Abstract: Background : To explore cognitive recovery during and after Narrative Exposure Therapy from the patient's perspective, autobiographical material and interview responses were qualitatively analyzed. Method : Using a framework of cognitive development, patient-reported outcomes from four senior Dutch citizens (57–81 years of age) were examined. All participants reported multiple traumatic experiences, including adverse childhood experiences. Results : During and after treatment, the participants reported gradual changes in posttraumatic feelings, cognitions, and treatment-related perceptions toward increased self-awareness and self-esteem. Conclusions : A framework of cognitive development provides a comprehensive understanding of how older adults deal with childhood trauma and its consequences.